THE CONTRIBUTION OF DIGITALIZATION IN THE DEVELOPMENT OF ASTRONOMY IN INDONESIA - Muhammad Awaludin; Nur Fajriani Zar'ah (Al-Hilal: Journal of Islamic Astronomy, 2022)
The Development of technology has a major impact on the development of Astronomy. The focus of this research is to analyze the impacts of the digitalization era on the development of Islamic astronomy discourses in Indonesia. This research is library research with a qualitative approach which aims to find out how the contribution of technology in the development of astronomy in Indonesia. The author's data sources in this study are scientific notes either in the form of books or notes from electronic media. The results of this study indicate that astronomy practitioners have made a new breakthrough in the development of astronomy, namely creating digital data-based applications to assist calculations. This scientific collaboration with technology and digitalization creates a harmony between astronomy and technology, thus making the study of astronomy in Indonesia more accommodating to digital era instead of just revolving around the study of science and religion.